Despite Praise: Techniques of Paradoxology and Paradoxography in the Work of Kyriakos Charalambides - Pylarinos, Theodosis (Études helléniques / Hellenic Studies, 2007)
Critics have often said that Kyriakos Charalambides’ poetry is hard and challenging even for the most cultivated and well-read reader. The author of the article examines the techniques of rhetoric style with which the poet orchestrates his inspirations: parentheses, stereotypical, corrective and introductory phrases, innuendoes, direct and indirect questions, comic scenes, etc.